Development and Validation of a Prognostic Nomogram for Prognosis in Patients With Renal Artery Stenosis - Li, Yan; Ma, Na; Zhang, Yuewei; Wang, Siyu; Sun, Youjing; Li, Mengpu; Ai, Hu; Zhu, Hui; Wang, Yang; Li, Peng; Guo, Fajin; Li, Yongjun; et al. (Frontiers in Medicine, 2022)
Renal artery stenosis (RAS) is associated with an increased risk of renal function deterioration (RFD). Our previous study showed that renal cortical blood perfusion assessed by CEUS was an important related factor for RFD in RAS patients. Based on several conventional related factors confirmed by previous studies, we aimed to establish and verify a CEUS+ scoring system to evaluate the risk of RFD at 1 year of follow up in RAS patients. This study was a single-center retrospective study. A total of 497 elderly RAS patients admitted to Beijing Hospital from January 2016 to December 2019 (247 in the training group and 250 in the verification group) were included. The baseline characteristics of the patients on admission and renal function (GFR) at 1-year of follow-up were collected. We used the univariate and multivariate logistic regression to establish a CEUS+ scoring system model, used the receiver operating characteristic (ROC) curve and area under the curve (AUC) to evaluate prediction accuracy, used the decision curve analysis and nomogram to evaluate the clinical application value. The baseline clinical-radiomic data of the training group and the verification group were similar (all P>0.05). Multivariate logistic regression analysis results showed that age (OR=1.937, 95%CI: 1.104-3.397), diabetes (OR=1.402, 95%CI: 1.015-1.938), blood pressure (OR=1.575, 95%CI: 1.138-2.182), RAS (OR=1.771, 95%CI: 1.114-2.816) and AUCi (OR=2.131, 95%CI:1.263-3.596) were related factors for RFD after 1 year of follow-up (all P<0.05). According to these results, the nomogram of the CEUS+ scoring system model was drawn, and its consistency index C-Index was 0.733 (95%CI: 0.653-0.822). 0.801, and the Youden index was 0.725 (specificity 0.768, sensitivity 0.813); the AUC of the ROC curve of the validation group was 0.853, Youden index was 0.718 (specificity 0.693, sensitivity 0.835); there was no significant difference in ROC curves between the two groups (D=1.338, P=0.325). In addition, the calibration charts of the model and verification group models showed that the calibration curve of the CEUS+ scoring system was close to the standard curve (P=0.701, P=0.823, respectively). The CEUS+ scoring system model is helpful to predict the risk of worsening renal function in elderly RAS patients.